Effects of theory-based education versus simulation-based training on knowledge and skills in managing shortness of breath among university health volunteers - Agus Nur Wahyuda; Marji Marji; Nurnaningsih Herya Ulfah; Anita Sulistyorini (CV Rezki Media, 2025)
Background: First aid skills for respiratory emergencies, particularly shortness of breath, are crucial for university health volunteers who often serve as the first responders. However, theory-based learning alone is not always adequate for developing practical competencies. Objectives: This study aims to evaluate the effectiveness of theoretical education compared to the combination of theory and simulation in enhancing the knowledge and skills of university health volunteers in managing cases of shortness of breath. Methods: A quasi-experimental pre-posttest design was conducted among 40 student volunteers of the Indonesian Red Cross Volunteer Corps (KSR-PMI), aged 18-20 years, who were equally assigned to a theory-only group or a theory-plus-simulation group. The intervention consisted of two 45-minute sessions. Knowledge and skills were assessed before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test and the Mann–Whitney U Test with a significance level of α = 0.05. Results: Knowledge significantly improved in both groups (p < 0.05), with no significant difference between them (p = 0.204). Skill performance improved markedly in the simulation group, increasing from 0% to 100%, compared with only 20% in the theory-only group (p < 0.001). Conclusions: While theoretical education effectively enhances knowledge, it is insufficient for developing practical skills. Integrating simulation-based training significantly improves psychomotor competence and better prepares university health volunteers to manage respiratory emergencies.